2022
DOI: 10.14202/vetworld.2022.2764-2771
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy skin disease: A newly emerging disease in Southeast Asia

Abstract: Lumpy skin disease (LSD) is caused by LSD virus (LSDV). This virus has been classified in the genus Capripoxvirus, family Poxviridae which generally affects large ruminants, especially cattle and domestic water buffalo. The first outbreak of LSD was found in 1929 in Zambia, then spreading throughout Africa and with an ongoing expanding distribution to Asia and Europe. In 2020, LSD was found from Southeast Asia in Vietnam and Myanmar before reaching Thailand and Laos in 2021. Therefore, LSD is a newly emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Most LSD illnesses are discovered in the summer when the vector is active. The increased risk of spreading LSD occurs during warmer and more humid summers which are able to support the breeding of vector populations (Ratyotha et al, 2022). This is in accordance with the statement of Namzi and Tafti (2021) that the risk factor for the spread of LSD is a warm and humid climate which is able to support the breeding of vector populations, as seen in the rainy season and the introduction of new animals to the herd.…”
Section: Transmissionsupporting
confidence: 87%
See 3 more Smart Citations
“…Most LSD illnesses are discovered in the summer when the vector is active. The increased risk of spreading LSD occurs during warmer and more humid summers which are able to support the breeding of vector populations (Ratyotha et al, 2022). This is in accordance with the statement of Namzi and Tafti (2021) that the risk factor for the spread of LSD is a warm and humid climate which is able to support the breeding of vector populations, as seen in the rainy season and the introduction of new animals to the herd.…”
Section: Transmissionsupporting
confidence: 87%
“…The virus that causes LSD has a diameter of 230-260 nm, is oval in shape, has a lipid envelope, replicates in the cytoplasm and has a double-stranded DNA genome with a length of about 151 kbp which consists of a central coding region bounded by identical 2.4 kbp inverted terminal repeats and is thought to contain 156 gen. Comparison of LSD viruses with Chordopoxviruses from other genera revealed that 146 conserved protein-coding genes are involved in transcription and mRNA biogenesis, nucleotide metabolism, DNA replication, protein processing, virion structure formation, virulence and host range (Ratyotha et al, 2022;Gumbe, 2018;Tulman et al, 2001). This virus has a close genome similarity (96%) with sheep pox and goat pox viruses but is phylogenetically different (Sendow et al, 2021).…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…used to obtain protection against LSD virus in cattle in various LSD endemic countries [12,15]. Some of the scientists recommended heterologous vaccine instead of homologous strain as use of homologues vaccine might have induced recombinant strain that can challenge the existing heterologous vaccine.…”
Section: Discussionmentioning
confidence: 99%